Doktrin Gereja : Eklesiologi - Martha Tesalonika; Irma Nelyani; Karina Onmilka; Sarmauli Sarmauli (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Ecclesiology, also known as church doctrine, is a field in Christian theology that examines the character, structure, mission, and role of the church as a religious institution. The study of ecclesiology highlights the relationship between the church and God, its people, and the world, and examines how the church plays a role in salvation and ministry. Aspects discussed in ecclesiology include the origins of the church, authority and hierarchy, sacraments, and the church’s obligations in evangelization. Apart from that, this doctrine also underlines the importance of unity, holiness and social responsibility of the church amidst the challenges of the times. Through ecclesiology, the church affirms its identity as a community of believers called to carry out a divine mission in the world.